Determining MUAP Activity Corridor In Scanning EMG Recordings - Artug, N. Tugrul; Bolat, Bulent; Osman, Onur; Goker, Imran; Baslo, M. Baris (IEEE, 2015)
In scanning EMG recordings there are more than one motor unit activity which is recorded by concentric needle electrode. Especially for determining features of a motor unit action potential (MUAP) such as phase duration and number of peaks easily, first the other motor unit activities must be discarded. In this study a new method is proposed to determine the activity corridor that related with the motor unit to be examined in scanning EMG recordings. This method is comprised of wavelet transform based noise reduction and autocorrelation function based location detection. Number of 34 scanning EMG recordings was tested by using this method and the activity corridors were determined correctly.
Keywords: Scanning EMG; neuromuscular diseases; activity corridor; wavelet transform; autocorrelation function; ELECTROMYOGRAPHY; Computer Science